Path planning in multi-scale ocean flows: Coordination and dynamic obstacles. (October 2015) - Lolla, T.; Haley Jr., P.J.; Lermusiaux, P.F.J.
Highlights: Derived level-set methodology for distance-based coordination of multiple vehicles operating in minimum time in ocean flows. Ocean currents, short-term reachability sets, and optimal headings are predicted for dynamic formation control. Obtained an efficient, non-intrusive technique for level-set-based time-optimal path planning within moving obstacles. Time-optimal paths that avoid moving obstacles and sustain the desired coordination are exemplified for varied ocean flows. Results are analyzed for the complex Philippine Archipelago, using data assimilative two-way nested reanalyses of currents. Abstract: As the concurrent use of multiple autonomous vehicles in ocean missions grows, systematic control for their coordinated operation is becoming a necessity. Many ocean vehicles, especially those used in longer-range missions, possess limited operating speeds and are thus sensitive to ocean currents. Yet, the effect of currents on their trajectories is ignored by many coordination techniques. To address this issue, we first derive a rigorous level-set methodology for distance-based coordination of vehicles operating in minimum time within strong and dynamic ocean currents. The new methodology integrates ocean modeling, time-optimal level-sets and optimization schemes to predict the ocean currents, the short-term reachability sets, and the optimal headings for the desired coordination. Schemes are developed for dynamic formation control, where multiple vehicles achieve and maintain a given geometric pattern as they carry out their missions. To do so, a new score function that is suitable for regular polygon formations is obtained. Secondly, we obtain an efficient, non-intrusive technique for level-set-based time-optimal path planning in the presence of moving obstacles. The results are time-optimal path forecasts that rigorously avoid moving obstacles and sustain the desired coordination. They are exemplified and investigated for a variety of simulated ocean flows. A wind-driven double-gyre flow is used to study time-optimal dynamic formation control. Currents exiting an idealized strait or estuary are employed to explore dynamic obstacle avoidance. Finally, results are analyzed for the complex geometry and multi-scale ocean flows of the Philippine Archipelago.